2018
DOI: 10.1021/acschemneuro.8b00222
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Sensitive Pull Down of Amyloid Fibrils Produced in Vitro and in Vivo by the Use of Pentameric-Thiophene-Coupled Resins

Abstract: Protein aggregation is a hallmark of several degenerative diseases, including Alzheimer's disease, Parkinson's disease and familial amyloidosis (Finnish type) (FAF). A method to isolate and detect amyloids is desired for the diagnosis of amyloid diseases. Here, we report the synthesis of pentameric thiophene amyloid ligand (p-FTAA) linked to agarose resin for selective purification of amyloid aggregates produced in vitro and in vivo. Using amyloid fibrils produced in vitro from α-synuclein, gelsolin, and Aβ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Recently, p-FTAA has also been utilized for the super resolution imaging of α-synuclein 113 and for the detection and purification of amyloid aggregates. 114 There are several advantages of using p-FTAA including the fact that it is a binding activated probe, that is, fluorescence is only reported when the molecule binds amyloid, and subsequently, no prelabeling steps are required.…”
Section: Luminescent Conjugated Polythiophene (Lcp)mentioning
confidence: 99%
“…Recently, p-FTAA has also been utilized for the super resolution imaging of α-synuclein 113 and for the detection and purification of amyloid aggregates. 114 There are several advantages of using p-FTAA including the fact that it is a binding activated probe, that is, fluorescence is only reported when the molecule binds amyloid, and subsequently, no prelabeling steps are required.…”
Section: Luminescent Conjugated Polythiophene (Lcp)mentioning
confidence: 99%
“…Then, we produced in vitro α-syn oligomers as described previously. 38 The oligomers were purified and then characterized by different techniques: transmission electron microscopy (Figure 4C) and dot blot with the antibody A11, which is selective for oligomers 39 (Figure 4D). It is important to note that the oligomeric characterization described in Figure 4C,D does not exclude the presence of other species of α-syn conformers such as monomers and small fibrils.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We observed that incubation with 30 or 60 μM MPs for 24 h caused no cytotoxicity in N2A cells (Figure B). Then, we produced in vitro α-syn oligomers as described previously . The oligomers were purified and then characterized by different techniques: transmission electron microscopy (Figure C) and dot blot with the antibody A11, which is selective for oligomers (Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…Other groups and ourselves have presented evidence that EGCG competes with ThT for some amyloid binding sites. , Luminescent-conjugated polythiophenes have been used to study protein aggregates in vitro, in situ, and in vivo . Among the conjugated polythiophenes, pentameric thiophene (pentameric formyl thiophene acetic acid (PFTAA), Figure S1C) exhibits conformation-dependent spectral properties, and when immobilized into agarose beads, it was able to pull down amyloid aggregates . Herein, we compare the ThT and PFTAA fluorescence as a readout of the EGCG remodeling activity against mature amyloid fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…27 Among the conjugated polythiophenes, pentameric thiophene (pentameric formyl thiophene acetic acid (PFTAA), Figure S1C) exhibits conformation-dependent spectral properties, 27 and when immobilized into agarose beads, it was able to pull down amyloid aggregates. 28 Herein, we compare the ThT and PFTAA fluorescence as a readout of the EGCG remodeling activity against mature amyloid fibrils.…”
Section: ■ Introductionmentioning
confidence: 99%